2019
DOI: 10.1002/ar.24292
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril Ameliorates Hepatic Ischemia Reperfusion Injury Via Regulation of NF‐κB‐p65/TLR‐4, JAK1/STAT‐3, Nrf‐2, and PI3K/Akt/mTOR Signaling Pathways

Abstract: Hepatic ischemia reperfusion (IR) is an inevitable clinical problem for surgical procedures such as liver transplantation and liver resection. This study was designed to evaluate the protective effect of perindopril (PER) against hepatic IR injury. Thirty‐two rats were used and randomly allocated into four groups. Sham control group was subjected to sham operation and received saline only, IR group was subjected to IR and received vehicle, PER group was pretreated with PER (one milligram per kilogram per day i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 61 publications
4
17
0
Order By: Relevance
“…It has been proposed that oxidative stress is a crucial contributor of I/R‐induced neuronal injury (Kamel, Hassanein, Ahmed, & Ali, 2019). Therefore, the level of oxidation‐related markers was measured.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that oxidative stress is a crucial contributor of I/R‐induced neuronal injury (Kamel, Hassanein, Ahmed, & Ali, 2019). Therefore, the level of oxidation‐related markers was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic IR resulted in hepatic injury as proved by increased level of liver enzymes. Hepatic IR causes the disruption of the membrane stability of hepatocytes due to necrosis, cellular damage, and structural changes with release of large quantities of liver enzymes [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that IR results in increased gene expression of both nuclear factor kappa B (NF-kβ) and Toll-like receptor 4 (a protein involved in both innate and adaptive immune system response), which constantly increased TNF-α leading to liver damage [38,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the liver biochemical indicator levels revealed considerable liver cell injury. AST, ALT, and ALP are biomarkers of liver function [31]. ALT is mainly distributed in hepatocyte cytoplasm, and elevated ALT levels indicate damage of hepatocyte membrane.…”
Section: Discussionmentioning
confidence: 99%